PENGARUH PERCEIVED TRUSTWORTHINESS, PERCEIVED RISK DAN PERCEIVED EASE OF USE TERHADAP MINAT BELI KONSUMEN PADA TOKO ONLINE JD.ID DI KOTA PADANG - Nadya Nyssa; Rose Rahmidani (Jurnal Ecogen, 2019)
This study aims to know and prove how much influence perceived trustworthiness, perceived risk, and perceived ease of use to purchase intention at online shop JD.id in Padang City.This type of research is causative. The population in this study were peoples in Padang City. The samples were taken using Cochran formula with 100 respondents. This sampling technique is based on nonprobability sampling method. The type of data used in this study is primary data. Data analysis technique used multiple regression analysis technique using SPSS version 21.00. The results of this study indicate that: 1) Perceived trustworthiness has a positive significant effect on purchase intention (0,003<0,05), 2) Perceived Risk has not significant effect on purchase intention (0,665>0,05),  3) Perceived Ease Of Use has a positive significant effect on purchase intention (0,008<0,05).Keywords: Perceived Trustworthiness, Perceived Risk, Perceived Ease Of Use, Purchase Intention